Effects of Parent-Adolescent Relationship Quality on Youth Symptoms Amidst COVID-19 - Frances M. Lobo; Casandra J. Gomez Alvarado; Giselle De Leon; Valerie V. Salcido; Paula Sanchez-Hernandez; Gabriela L. Stein (Behavioral Sciences, 2025)
Amidst the health and socioeconomic burdens COVID-19 placed on families, communities of color also grappled with heightened xenophobia and racism. Yet, adolescents also found silver linings in the form of spending time with family and engaging in activities promoting relaxation and leisure. The present study examined parent-adolescent relationship quality (RQ) as a moderator of the relations of Latinx youth’s environment (i.e., racial-ethnic discrimination, COVID-19 stress, and COVID-19 silver linings) on their anxiety and depressive symptoms, both concurrently and six months later. Participants included 135 Latinx adolescents (Mage = 16.00, SD = 1.27; 59.3% female; 85.2% U.S.-born). Path analytic models revealed that youth discrimination experiences were positively associated with youth symptomatology, whereas COVID-19 silver linings and positive RQ were negatively associated with youth symptomatology. We also found that at mean and higher levels of negative RQ, discrimination experiences were positively associated with concurrent anxiety symptoms, suggesting that negative relationship features (e.g., conflict, pressure) exacerbated the effects of discrimination on youth anxiety. Therefore, stressors may predict youth symptomatology concurrently, but cultivating a positive parent-adolescent relationship and encouraging finding silver linings may bolster resilience in Latinx youth across time amidst adversity.